Digital Branding on Instagram and TikTok Driving Engagement for Cardboard Box Products - Mochamad Heru Riza Chakim; Mulyati; Septiani, Nanda; Nasution, Erni Juliana Al Hasanah; Perez, Carlos (Pandawan, 2025)
This study examines how digital branding on Instagram and TikTok, digital pro- motion, and product quality shape customer engagement and purchase intention in the packaging sector, using nuansa box indonesia Indonesia as the focal case. Gap research predominantly explores fashion, cosmetics, and F&B industries, leaving limited evidence on B2B/B2C packaging where products are often per- ceived as merely functional. We provide an in-depth case of a packaging brand and model the mediating role of customer engagement between digital strat- egy (branding, promotion) and purchase intention, estimated via PLS-SEM. The measurement model is robust (all loadings > 0.70; AVE > 0.50; Cronbach’s Alpha and Composite Reliability > 0.70). The structural model shows substan- tial explanatory power for purchase intention (R2 = 0.748). Product Quality is the strongest driver of Purchase Intention (β = 0.401), while Customer Engage- ment positively influences Purchase Intention (β = 0.288) and is significantly driven by Digital Branding (β = 0.489) and Digital Promotion (β = 0.375). The direct path from Digital Promotion to Purchase Intention is not significant (p = 0.060). Results indicate that compelling digital branding cultivates en- gagement that converts to purchase intention, but promotion alone is insufficient without strong product fundamentals. Managerially, firms should prioritize con- sistent, aesthetic branding to build engagement, leverage targeted promotions to activate trials, and sustain investment in product excellence as the ultimate lever of conversion and loyalty.